2000
DOI: 10.1054/bjoc.1999.0871
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerate mutase, 2,3-bisphosphoglycerate phosphatase, creatine kinase and enolase activity and isoenzymes in breast carcinoma

Abstract: We have compared the levels of phosphoglycerate mutase (EC 5.4.2.1), 2,3-bisphosphoglycerate phosphatase (EC 3.1.3.13), creatine kinase (EC 2.7.3.2) and enolase (EC 4.2.1.11) activities and the distribution of their isoenzymes in normal breast tissue and in breast carcinoma. Tumour tissue had higher phosphoglycerate mutase and enolase activity than normal tissue. Creatine kinase activity was higher in seven out of 12 tumours. In contrast 2,3-bisphosphoglycerate phosphatase activity was lower. Phosphoglycerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 56 publications
(76 reference statements)
5
56
0
3
Order By: Relevance
“…27 In addition, colorectal, liver, lung and breast carcinoma tissues contain mainly PGM-B and traces of PGM-MB and their PGM enzymatic activities are higher than those of adjacent normal tissues. 28,29 Brain tumours possessed lower PGM activity than normal brain. 30 In fibroblasts, exposure of the cells to hypoxia induces induction of PGM activity, concomitant with elevations of mRNA and the protein levels of PGM-B, indicating that the enzyme activity is regulated mainly at the transcriptional step.…”
Section: Discussionmentioning
confidence: 94%
“…27 In addition, colorectal, liver, lung and breast carcinoma tissues contain mainly PGM-B and traces of PGM-MB and their PGM enzymatic activities are higher than those of adjacent normal tissues. 28,29 Brain tumours possessed lower PGM activity than normal brain. 30 In fibroblasts, exposure of the cells to hypoxia induces induction of PGM activity, concomitant with elevations of mRNA and the protein levels of PGM-B, indicating that the enzyme activity is regulated mainly at the transcriptional step.…”
Section: Discussionmentioning
confidence: 94%
“…It has been recently shown that the oncogene P53 may regulate metabolic pathways by several novel genes, including PGAM. Also, PGAM expression levels are altered in brain, colon, breast, lung and liver cancers [6,9,8,7].…”
Section: Important Features For Lymphoma Datamentioning
confidence: 99%
“…is overexpressed in many cancers including lung, colon, liver and breast (Durany et al, 2000;Durany et al, 1997).…”
mentioning
confidence: 99%